Asesmen Afektif dalam Pembelajaran PAI Berbasis Cinta; Sebuah Tinjauan Konseptual untuk Penguatan Karakter Religius - Muhammad Dodi Alfiansyah; Lubna; Mukhlis (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Islamic Religious Education (IRE) plays a strategic role in shaping students’ religious character; however, learning evaluation in IRE remains predominantly cognitive-oriented, often neglecting affective dimensions that are central to character formation. This condition creates a gap between the ideal objectives of Islamic education and assessment practices in classrooms. Responding to this issue, this study aims to analyze the integration of affective assessment within love-based curriculum in Islamic Religious Education, examine its design and implementation, and explore its contribution to students religious character development. This research employs a qualitative approach using library research with a descriptive-conceptual design. Data were collected from scholarly journals, policy documents, and academic publications relevant to affective assessment, character education, Islamic education, and love-based curriculum. The data were analyzed using qualitative content analysis through data reduction, thematic categorization, and conceptual synthesis. The findings indicate that affective assessment based on a love-based curriculum shifts the assessment paradigm from judgment-oriented evaluation to humanistic and process-oriented assessment. Such integration emphasizes empathy, compassion, reflection, and meaningful teacher student relationships, enabling the internalization of Islamic values in students daily behavior. Furthermore, well-designed and authentically implemented affective assessment contributes significantly to the development of students religious character, including spiritual awareness, moral responsibility, and social ethics. This study implies that affective assessment should be positioned as an integral pedagogical instrument in Islamic Religious Education to support holistic and transformative learning aligned with the principles of love-based education.